1992
DOI: 10.1177/014107689208500211
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Alvarado Score in Acute Appendicitis

Abstract: Use of the Alvarado scoring system was assessed prospectively in a consecutive. series of 215 patients with suspected appendicitis over a 12 month period at the University Hospital of Wales, Cardiff. In comparison the high negative appendicectomy rate during the year prior to the study was reduced considerably with the scoring system without increasing morbidity or mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(22 citation statements)
references
References 2 publications
0
8
0
1
Order By: Relevance
“…Scoring systems have been designed to aid in the clinical assessment of patients with acute appendicitis. The Alvarado score is the most well known and best performing in validation studies, but it has some drawbacks [7][8][9]. Its construction was based on a review of patients who had been operated with suspicion of appendicitis, whereas the score is supposed to be used on all patients with suspicion of appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…Scoring systems have been designed to aid in the clinical assessment of patients with acute appendicitis. The Alvarado score is the most well known and best performing in validation studies, but it has some drawbacks [7][8][9]. Its construction was based on a review of patients who had been operated with suspicion of appendicitis, whereas the score is supposed to be used on all patients with suspicion of appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…AS has been shown to be highly valid when applied to populations in the United States and Europe. [14] In the study conducted by Tatli et al, [15] it was reported that the AS is an easy-to-use and noninvasive ancillary diagnostic tool with high diagnostic accuracy in patients with suspected AA. Parallel to this, in the study by Augustin et al patients with a score > 7 were associated with 82.9% sensitivity and 86.4% specivity.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly validated CPR was the Alvarado score, followed by the Kalan's modified Alvarado score (Figs. 2, 3) [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The average AUC value for the Alvarado score that ranged between 0.74 and 0.88 was higher than the modified Alvarado score which had an AUC of 0.69 from a single study (Table 5).…”
Section: Validation Studiesmentioning
confidence: 99%